2019
DOI: 10.1145/3323335
|View full text |Cite
|
Sign up to set email alerts
|

Dance Interactive Learning Systems

Abstract: Motion Capture and whole-body interaction technologies have been experimentally proven to contribute to the enhancement of dance learning and to the investigation of bodily knowledge, innovating at the same time the practice of dance. Designing and implementing a dance interactive learning system with the aim to achieve effective, enjoyable, and meaningful educational experiences is, however, a highly demanding interdisciplinary and complex problem. In this work, we examine the interactive dance training syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(28 citation statements)
references
References 53 publications
0
27
0
1
Order By: Relevance
“…It can help students understand the connotation of dance deeply and guide students to master the learned movements. It can also effectively improve teachers' demonstration and students' imitation of traditional teaching methods and increase the interaction between teachers and students [3]. Pham et al (2018) [4] showed that the computer vision community is currently committed to solving the problem of action recognition in real videos, which contain thousands of challenging samples.…”
Section: Introductionmentioning
confidence: 99%
“…It can help students understand the connotation of dance deeply and guide students to master the learned movements. It can also effectively improve teachers' demonstration and students' imitation of traditional teaching methods and increase the interaction between teachers and students [3]. Pham et al (2018) [4] showed that the computer vision community is currently committed to solving the problem of action recognition in real videos, which contain thousands of challenging samples.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, Raheb et al [38] propose an extensive literature review of interactive systems that support dance learning. The majority of the systems presented follow the same workflow: the system presents a "correct movement" that the student needs to reproduce while the system provides feedback.…”
Section: Annotation Systems In Dance Learningmentioning
confidence: 99%
“…Learning and performing a new dance choreography requires both skill and practice [21], and offers a fertile ground for studying complex skill acquisition [4,5]. Although a number of systems have been designed to teach dance [38], most of them focus on supporting an individual dancer's learning process [1]. However, learning a dance performance is highly collaborative -dancers must not only learn their own parts, but also learn how to interact dynamically with other dancers.…”
Section: Introductionmentioning
confidence: 99%
“…[82], and combinations of some [23], or all of them [3]. These interactive systems span many physical activities including yoga [84], rock climbing [38], snowboarding [82], skiing [30], swimming [3], squats and deadlifts [23], slackline [2], golf training [36], and dancing [66].…”
Section: Introductionmentioning
confidence: 99%